Waste Recycling Of Industrial By-Products In The Preparation Of Mortars - Badaoui Azhar, Moussaoui Hayet (International Journal of Advanced Science and Technology, 2020)
The aim of this study is the valorization of marble powder as an addition in cementitious matrix construction materials. The main aim of this study is to highlight the possibility of recycling marble waste and using it as an addition in mortars.